PELAKSANAAN KONSELING KELOMPOK DALAM MENGATASI MASALAH SUSAH BANGUN PAGI PADA SISWA - Fatheni Cova Kamil Khairy; Darimis (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
The purpose of this study is to examine the implementation of group counseling for students and to describe the process of group counseling services in addressing students’ difficulties in waking up early. This study employed a qualitative method with a descriptive approach, and the data were collected through observations and interviews conducted with guidance and counseling teachers and tenth-grade students at SMA N 1 Koto Besar, Dharmasraya Regency. The results indicate that the implementation of group counseling was carried out through several stages, namely the formation stage, transition stage, activity stage, and termination stage. The Islamic integrative Cognitive Behavioral Therapy (CBT) approach was effective in helping students identify maladaptive thinking patterns and transform them into more positive and rational ones, as well as in fostering awareness to develop the habit of waking up early. These findings contribute to the development of guidance and counseling services in schools and strengthen the effectiveness of Islamic integrative CBT within the context of group counseling.